Porous nickel-based electrocatalyst containing cation defects and preparation method of porous nickel-based electrocatalyst
By introducing cationwear defects and porous structures in electrolytic water hydrogen cathode materials, using silicon nanochromes and water synthesis technology to solve the problem of complexity and stability in the existing technologies, and achieve efficient electrical catalytic catalytic catalytic catalytic catalytic catalysts Hydrogen analysis and electrochemical stability.
Patent Information
- Application Number
- CN202411577537.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
The synthesis process of existing electrolytic water-based hydrogen cathode materials is complex, the conditions are rigorous, and the modification methods are single, and the long-term stability needs to be examined.
Through appearance regulation and defective engineering means, prepare a porous nickel -based catalyst with cationic defects, and use single decentralized silica nano -ball balls as pore makers, combined with water heat synthesis and alkaline liquid etching technology to improve the surface area of the material and the surface area and The charge transmission rate.
The efficient electrochemical stability and electrocatalyst hydrogen analysis of catalysts are realized. It is suitable for ALK and AEM electrolytic hydrogen -making technology, which has excellent electrocatalytic hydrogen analysis properties and high stability.
Smart Images

Figure CN119372694A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a porous nickel-based electrocatalyst containing cation defects and a preparation method thereof. Background Art
[0002] The main technologies for producing hydrogen by electrolysis of water at present include: alkaline water electrolysis (ALK) hydrogen production technology, proton exchange membrane (PEM) water electrolysis hydrogen production technology, anion exchange membrane (AEM) water electrolysis hydrogen production technology and solid oxide (SOEC) water electrolysis hydrogen production technology. Among them, ALK hydrogen production technology is the most mature and is the earliest industrialized water electrolysis hydrogen production technology in China, and AEM hydrogen production technology has also emerged in the market. Electrocatalytic water decomposition includes two steps that are carried out simultaneously: the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Limited by the reaction kinetics, it is usually necessary to overcome a high overpotential to drive the reaction, and the use of the corresponding catalyst can effectively reduce the reaction overpotential to achieve efficient water decomposition. For HER, nickel-based hydrogen evolution electrodes have attracted much attention due to their high electrocatalytic activity and low cost.
[0003] The existing cathode materials for hydrogen production by water electrolysis are mainly based on Ni-based materials. The molecular structure is designed through morphology control, heterogeneous structure construction, multi-metal doping and other means to improve the exposure of the effective active components of the material and the rapid conduction of charge, thereby achieving the improvement of hydrogen evolution efficiency and the reduction of energy consumption. However, the synthesis scheme of its catalyst material still has problems such as complex process, strict conditions, single modification method, and long-term stability needs to be investigated.
[0004] Patent CN 110607532 A discloses a method for preparing Co-Ni-P / fs-Si material for electrolysis of water for hydrogen evolution. The invention mainly uses femtosecond laser processing technology to etch silicon to obtain fs-Si with a porous structure. Then, it uses this as a substrate to synthesize cobalt nickel precursor / fs-Si material under acidic conditions by hydrothermal method, and then performs phosphating treatment to obtain Co-Ni-P / fs-Si electrocatalyst material. The material exhibits excellent performance of electrolysis of water for hydrogen evolution. -1 In H2SO4 solution, 10 mA cm -2The required potential is only 69mV. Patent CN116065184 A describes a porous nickel-supported nickel-based electrocatalyst, its preparation method and application in water electrolysis to hydrogen production. The method mainly includes using nickel foam as the negative electrode and a stone mill rod as the positive electrode, and in-situ growth of NiO film by constant current rapid electrodeposition in a combined electrolyte of NiCl2·6H2O and NH4Cl, and then using this as a substrate, placing it in a reaction solution containing NiNO3·6H2O and Na2MoO4·4H2O for heat treatment, and performing phosphating treatment to finally obtain a porous nickel-supported nickel-based electrocatalyst. The catalyst has excellent electrocatalytic activity, can meet the efficient operation of a variety of electrocatalytic reactions, and effectively reduces the energy consumption of the hydrolysis hydrogen production process. Patent CN 104843805 A describes a method for preparing a three-dimensional nanomaterial with a CNTs@SiO2@Ni / Al-LDH core-shell structure. The material is formed by coating the surface of carbon nanotubes with SiO2 shells to form a core-shell structure, and coating the outer layer of the core-shell structure with AlOOH sol, and synthesizing the CNTs@SiO2@Ni / Al-LDH core-shell structure electrode material in situ by hydrothermal method. The material has a large specific surface area, which can realize rapid charge transfer and thus has stable electrochemical properties. The above three patents carry out molecular design for the morphology regulation of Ni-based materials. The sample has a large specific surface area and can effectively realize the effective exposure of the active sites of the material, but the synthesis process requires the template material to be pre-treated first, and then the catalyst powder is loaded in situ according to the experimental route. The steps are cumbersome, the processing is delicate, and the yield is low, which is not technically economical.
[0005] Patent CN 109280811A describes a nickel-based porous cathode material for electrolytic hydrogen evolution and its preparation method. The invention mainly involves mixing high-purity powders of Ni, Fe, Mo, and Mn in a certain mass percentage, adding glue and drying, and then pressing and molding to obtain a green body, and using the principle of solid-phase partial diffusion to vacuum sinter the green body to synthesize Ni-Fe-Mo-Mn porous materials. The prepared nickel-based porous material has the advantages of large specific surface area, low hydrogen evolution overpotential, excellent corrosion resistance, stable working performance, simple and environmentally friendly preparation process, etc. The specific surface area of the material is improved due to the porous structure, thereby promoting the rapid progress of the hydrogen evolution reaction. However, the sintering temperature required for multi-metals is relatively high, and it needs to be in a vacuum environment. The harsh reaction conditions hinder the reproducibility and large-scale preparation of the material.
[0006] Patent CN 116288456 A adds organic molecules to form a mixed homogeneous electrolyte, uses negatively charged and unsaturated organic molecules to improve the activity of the electrodeposited nickel-based catalyst, and realizes a one-step electrodeposition method to prepare Ni-based electrocatalytic materials. The process is simple and has strong applicability, but its modification method is single, and only a Ni monolayer catalyst electrode is formed, which has a small specific surface area and has limited improvement on the electrocatalytic performance of the material. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a porous nickel-based electrocatalyst containing cation defects and a preparation method thereof, and designs the molecular structure of the hydrogen evolution Ni-based material through morphology control and defect engineering means, thereby improving the specific surface area of the catalyst, increasing the cation vacancies of the catalyst, and enhancing the charge transfer power, thereby improving its electrocatalytic hydrogen evolution activity, and solving the above-mentioned technical problems.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing a porous nickel-based electrocatalyst containing cation defects, comprising the following steps:
[0009] S1 raw material mixing: a solution formed by dissolving a certain amount of pore-forming agent in water is mixed with a solution formed by dissolving a certain amount of precursor in a certain amount of deionized water, and the mixture is mixed by ultrasonic and mechanical stirring for 2 hours; the pore-forming agent is monodisperse silica microspheres with a particle size of 20-40 nm; the precursor includes soluble nickel salt, soluble aluminum salt, chitosan and accelerator;
[0010] S2 hydrothermal synthesis: the mixed solution in step 1 is transferred to a polytetrafluoroethylene hydrothermal reactor, and then placed in an oven for constant temperature reaction. After the reaction is completed, the temperature is naturally lowered to ambient temperature, taken out, and centrifuged to obtain a precipitate, which is the reaction product;
[0011] S3 alkali solution etching: The reaction product of step 2 was ultrasonically dispersed again in 50 mL of deionized water, and transferred to one side of the H-type reactor. 50 mL of alkali solution was added to the other side. An anion exchange membrane was placed in the middle of the channel. The mixture was stirred for 12-36 hours for dialysis. The temperature was set to 50-70°C and the stirring speed was set to 200 rpm.
[0012] S4 washing and drying: the sample etched in step 3 is washed several times with deionized water and ethanol until the pH of the sample is neutral, and the washed sample is placed in an oven at 60° C. and dried for 12 h to obtain a porous nickel-based electrocatalyst (mNiAl-LDH) containing cation defects;
[0013] S5 electrochemical performance test: 1 mol·L -1 The electrochemical properties of the porous nickel-based electrocatalyst material containing cation defects obtained in step four of the three-electrode test system were tested using KOH as electrolyte, Pt sheet as counter electrode, Hg / HgO as reference electrode, and ITO conductive glass loaded with the sample as working electrode.
[0014] Furthermore, the mixing for 2 hours in step 1 means ultrasonication for 30 minutes and then magnetic stirring at a speed of 300 rpm for 30 minutes, alternating in sequence and uniformly mixing for 2 hours.
[0015] Furthermore, the silica microspheres in step 1 are dissolved in water to form a silica dispersion having a concentration of 10% w / v.
[0016] Furthermore, in step 1, the soluble nickel salt is one of nickel nitrate, nickel sulfate and nickel chloride, the soluble aluminum salt is one of aluminum nitrate, aluminum sulfate and aluminum chloride, and the promoter is one of urea and hexamethylenetetramine (HMT).
[0017] Furthermore, in step 1, the molar ratio of the promoter / soluble nickel salt is 1:1-5:1, the molar ratio of the soluble nickel salt / soluble aluminum salt is 1:1-5:1, the molar ratio of the pore-forming agent / soluble nickel salt is 5:1-14:1, and the molar ratio of chitosan to the soluble nickel salt is 1:10-1:15; the amount of deionized water used is 65wt% of the total mass of the solution.
[0018] Furthermore, the reaction temperature of step 2 is increased from 30°C at a rate of 1°C / min to 100-140°C, and the reaction is maintained at a constant temperature for 12-48 hours.
[0019] Furthermore, the alkali solution in step 3 is one of NaOH and KOH solutions, with a concentration of 6-10 mol·L -1 ; The thickness of the anion exchange membrane is 20-50μm.
[0020] Compared with the prior art, the present invention provides a porous nickel-based electrocatalyst containing cation defects and a preparation method thereof, which has the following beneficial effects:
[0021] 1. The present invention controls the ratio of precursor raw materials to prepare two-dimensional NiAl-LDH with uniform morphology and high crystallinity; adds monodisperse silica nanospheres as pore-forming agents to increase the specific surface area of the material, synthesizes the product in one step by hydrothermal method, and reduces the preparation process of the product; etches the product with alkaline solution after dialysis to achieve the formation of mesoporous structure and selectively leach only Al components to form cationic vacancy defects, thereby improving the charge transfer rate of the material; the obtained product has excellent electrochemical stability and electrocatalytic hydrogen evolution performance.
[0022] 2. The porous nickel-based electrocatalyst containing cation defects of the present invention is suitable for the cathode catalyst of ALK hydrogen production technology or AEM water electrolysis hydrogen production technology, with an applicable temperature of 30-80°C and high stability within 12 hours. -1 In a three-electrode test system with KOH as electrolyte, Pt sheet as counter electrode, Hg / HgO as reference electrode and the prepared sample as working electrode, the -2 The overvoltage at a current density of 100 mV (vs RHE) is excellent for electrocatalytic hydrogen evolution.
[0023] 3. The catalyst obtained by the present invention has the advantages of complete grain growth and small particle size, and the raw materials are cheap and easily available; the addition of nano-silica pore-forming agent increases the interlayer spacing of the molecular structure, and after etching with alkaline solution, a large number of mesoporous structures are formed, which increases the specific surface area of the material and enhances the exposure of active sites; and the alkaline solution can selectively dissolve the Al component in the material, and only introduces additional Al vacancy defects without causing other types of defects, thereby forming cation vacancy defects, providing a channel for high-speed charge transmission, and improving its electrochemical hydrogen evolution activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a flow chart of the preparation process of Example 1 of the present invention;
[0025] Figure 2 is a hydrogen evolution polarization curve diagram of Example 1 of the present invention;
[0026] Figure 3 This is a nitrogen isotherm adsorption curve diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The porous nickel-based electrocatalyst containing cation defects of the present invention has a final product of porous NiAl layered double hydroxide (mNiAl-LDH), which has a large specific surface area and has cation vacancy defects. The porous nickel-based electrocatalyst containing cation defects of the present invention is suitable for the cathode catalyst of ALK hydrogen production technology or AEM water electrolysis hydrogen production technology, and the applicable temperature is 30-80°C. The porous nickel-based electrocatalyst containing cation defects of the present invention is 1 mol·L -1 In a three-electrode test system with KOH as electrolyte, Pt sheet as counter electrode, Hg / HgO as reference electrode and the prepared sample as working electrode, the -2 The overvoltage at a current density of 100 mV (vs RHE) is excellent for electrocatalytic hydrogen evolution.
[0029] See also Figure 1-3 , a method for preparing a porous nickel-based electrocatalyst containing cation defects, comprising the following steps:
[0030] S1 Raw material mixing: a solution formed by dissolving a certain amount of pore former in water is mixed with a solution formed by dissolving a certain amount of precursor in a certain amount of deionized water, and mixed for 2 hours by ultrasonic and mechanical stirring. Mixing for 2 hours means ultrasonication for 30 minutes and then magnetic stirring at a speed of 300 rpm for 30 minutes, and the mixture is rotated in sequence and uniformly mixed for 2 hours.
[0031] The pore-forming agent is monodispersed silica microspheres with a particle size of 20-40 nm; the appropriate mesoporous structure is conducive to the construction of a fast charge transmission channel and promotes the desorption of hydrogen in the hydrogen evolution reaction. The silica microspheres are dissolved in water to form a silica dispersion with a concentration of 10% w / v.
[0032] The precursor includes a soluble nickel salt, a soluble aluminum salt, chitosan and an accelerator. The soluble nickel salt is one of nickel nitrate, nickel sulfate and nickel chloride, the soluble aluminum salt is one of aluminum nitrate, aluminum sulfate and aluminum chloride, and the accelerator is one of urea and hexamethylenetetramine (HMT). The molar ratio of the accelerator / soluble nickel salt is 1:1-5:1, the molar ratio of the soluble nickel salt / soluble aluminum salt is 1:1-5:1, the molar ratio of the pore former / soluble nickel salt is 5:1-14:1, and the molar ratio of chitosan to the soluble nickel salt is 1:10-1:15. The amount of deionized water used is 65wt% (relative to the total mass of the solution).
[0033] The amount of promoter and precursor added will directly affect the morphology of the product. For example, excessive addition may form needle-shaped LDH. The pore design in the present invention is based on the sheet structure of the product. The network structure formed by the coordination of chitosan and metal ions can effectively avoid the agglomeration of metal particles and improve the crystallinity of the material. The content of the pore-forming agent directly affects the porous structure of the material. The right amount of mesopores is conducive to increasing the specific surface area of the material and improving the efficient reaction of the active sites. Too many pores are prone to charge accumulation, making it difficult for gas to escape during hydrogen evolution, and increasing the gas-liquid transmission impedance.
[0034] S2 hydrothermal synthesis: transfer the mixed solution in step 1 to a polytetrafluoroethylene hydrothermal autoclave, and then put it into an oven for constant temperature reaction. Start heating from 30°C at a heating rate of 1°C / min. When the reaction temperature reaches 100-140°C, maintain the constant temperature reaction for 12-48h. After the reaction is completed, cool it naturally to ambient temperature, take it out, and obtain the precipitate by centrifugation, which is the reaction product.
[0035] S3 alkali solution etching: The reaction product was ultrasonically dispersed again in 50 mL of deionized water, transferred to one side of the H-type reactor, and 50 mL of alkali solution was added to the other side. An anion exchange membrane was placed in the middle of the channel, and the dialysis was stirred for 12-36 hours. The temperature was set to 50-70 ° C and the stirring speed was 200 rpm. The alkali solution was one of NaOH and KOH solutions with a concentration of 6-10 mol·L-1 Only OH is allowed - Participate in the alkaline etching reaction without introducing impurities. The concentration of the alkaline solution should not be too high. High-concentration alkaline solution can easily cause the Ni group to precipitate and generate Ni(OH)2 while etching the template and selectively leaching the Al component, causing irreversible damage to the intrinsic structure of the product. The thickness of the anion exchange membrane is 20-50μm.
[0036] S4 washing and drying: the sample etched with alkaline solution after dialyzing through anion exchange membrane in step 3 is washed several times with deionized water and ethanol until the pH of the sample is neutral. The washed sample is placed in an oven at 60°C and dried for 12 hours to obtain a porous nickel-based electrocatalyst (mNiAl-LDH) containing cation defects.
[0037] S5 electrochemical performance test: 1 mol·L -1 The electrochemical properties of the porous nickel-based electrocatalyst material containing cation defects obtained in step four of the three-electrode test system were tested using KOH as electrolyte, Pt sheet as counter electrode, Hg / HgO as reference electrode, and ITO conductive glass loaded with the sample as working electrode.
[0038] Embodiment 1:
[0039] S1 raw material mixing: take 20mL silica dispersion (10% w / v), 1.36g nickel nitrate, 0.58g aluminum nitrate, 0.92g HMT, 0.063g chitosan and 40mL deionized water, ultrasonicate for 30min, then magnetically stir at 300rpm for 30min, rotate in sequence, and mix evenly for 2h.
[0040] S2 Hydrothermal synthesis: Transfer the mixed homogeneous solution to a polytetrafluoroethylene hydrothermal reactor and place it in an oven for hydrothermal reaction. Set the temperature program to 30-120°C, with a heating rate of 1°C / min, keep the temperature at 120°C for 24 hours, then cool it naturally to 25°C, take it out and centrifuge it to obtain the precipitate, which is the reaction product.
[0041] S3 Alkaline solution etching: The product was ultrasonically dispersed in 50 mL of deionized water and transferred to one side of the H-type reactor. On the other side, 50 mL of 8 mol·L -1 NaOH solution, an anion exchange membrane is placed in the middle of the channel, and the solution is slowly stirred to react for 24 hours at a stirring speed of 200 rpm.
[0042] S4 washing and drying: the sample treated with alkali solution was filtered and washed several times with deionized water and ethanol until the pH value of the sample was neutral, and then placed in an oven at 60°C for 12 hours to obtain a porous nickel-based electrocatalyst (mNiAl-LDH) containing cation defects.
[0043] S5 electrochemical performance test: 1 mol·L-1 The electrochemical properties of the material were tested in a three-electrode test system with KOH as electrolyte, Pt sheet as counter electrode, Hg / HgO as reference electrode and ITO conductive glass loaded with sample as working electrode.
[0044] S6 Comparison of specific surface area of samples before and after optimization: The test method is to take 100 mg of sample for nitrogen isothermal adsorption and desorption test, where the degassing time is 12 h and the temperature is 120 ° C. The results are shown in Table 1.
[0045] Embodiment 2:
[0046] The difference from Example 1 is that the added amount of aluminum nitrate is 1.77 g.
[0047] Embodiment 3:
[0048] The difference from Example 1 is that the amount of accelerator HMT added is 1.97g.
[0049] Embodiment 4:
[0050] The difference from Example 1 is that the added amount of chitosan is 0.076 g.
[0051] Embodiment 5:
[0052] The difference from Example 1 is that the added amount of the pore-forming agent silica dispersion is 30 mL.
[0053] Table 1 Comparison of specific surface areas of Examples 1-5 of the present invention and the comparative example
[0054]
[0055] In Table 1, the literature reference example refers to the NiAl-LDH sample described in the literature: Highly efficient catalytic hydrogenolysis of lignin model compounds over hydrotalcite-derived Ni / Al2O3 catalysts (Gao H., Qiu L., Wu F., et al. 2023.).
[0056] S BET (m 2 ·g -1 ) refers to: the surface area of the material, that is, the total area per unit mass of the material, S BET (m 2 ·g -1 ) is higher, indicating that the same mass of material has a richer pore structure, presenting a larger surface area and providing a large number of catalytic active sites.
[0057] η100 (mV vs RHE) refers to the data obtained by linear voltammetry test of the material at 100mA·cm -2 The overpotential relative to the hydrogen electrode at the current density, η 100 The lower the (mV vs RHE) value, the lower the overpotential at the same current density, and the lower the power consumption, that is, the higher the current efficiency and the better the electrolysis catalysis.
[0058] It can be seen from Table 1 that the increase in the amount of aluminum nitrate added in Example 2 will increase the BET (m 2 ·g -1 ) value is greatly reduced, η 100 (mV vs RHE) value slightly increased; the increase in the amount of accelerator HMT in Example 3 will make S BET (m 2 ·g -1 ) value is slightly reduced, η 100 The performance characteristics of the above two groups of examples show that the appropriate amount of precursor added has an impact on the assembly of its sheet structure, thereby affecting the specific surface area and electrochemical activity of the sample. In Example 4, the amount of chitosan added was slightly increased, which would increase the S BET (m 2 ·g -1 ) value is greatly reduced, η 100 The (mV vs RHE) value slightly increased, mainly because the coordination relationship between chitosan and metal ions was enhanced, which increased the degree of structural polymerization, thereby causing a decrease in the specific surface area of the sample and a weakening of the electrocatalytic performance; in Example 5, the addition amount of the silica dispersion was increased by half, which would make S BET (m 2 ·g -1 ) value is greatly improved, η 100 The (mV vs RHE) value increases, and the overly rich pore structure makes it possible for charge recombination and gas product desorption to be difficult, which in turn causes an increase in overpotential, that is, a decrease in current efficiency. Therefore, an appropriate and moderate synthesis formula promotes the optimization of the electrochemical hydrogen evolution performance of the sample.
[0059] like Figure 2 As shown in the polarization curve test of hydrogen evolution reaction, at a current density of 100 mA cm -2 (η 100 ) is 143 mV (vs RHE), which shows excellent electrocatalytic hydrogen evolution performance. After 12 h constant voltage test, the material shows no obvious voltage decay, indicating that it has high electrochemical stability.
[0060] like Figure 3As shown in the nitrogen isotherm adsorption curve, the specific surface area test result of Example 1 is 121m 2 ·g -1 , showing a certain active area advantage in all embodiments, and having significantly excellent electrochemical hydrogen evolution performance.
[0061] The present invention discloses a porous nickel-based electrocatalyst containing cation defects and a preparation method thereof. The monodisperse silica nanospheres are used as pore-forming agents, and are uniformly mixed with basic raw materials such as soluble nickel salts, soluble aluminum salts, promoters, chitosan, and deionized water. The homogeneous mixed solution is then transferred to a polytetrafluoroethylene hydrothermal reactor for hydrothermal reaction. After the reaction is completed, the mixture is etched with alkaline solution, and finally washed and dried. The molar ratio of promoter / soluble nickel salt is 1:1-5:1, the molar ratio of soluble nickel salt / soluble aluminum salt is 1:1-5:1, the molar ratio of pore-forming agent / soluble nickel salt is 5:1-14:1, and the molar ratio of chitosan to soluble nickel salt is 1:10-1:15. When the promoter is slowly hydrolyzed to produce OH - Under the action of, the solubility of soluble nickel salts and soluble aluminum salts in water is used to achieve recrystallization and precipitation. The rich functional groups on the chitosan carbon chain interact with metal ions, regulate the orderly arrangement of metal ions, and promote the crystallization of the material in two dimensions, thereby forming ultrathin NiAl layered double hydroxide (NiAl-LDH). The synthesized material has the advantages of complete grain growth and small particle size, and the raw materials are cheap and easy to obtain, which is an environmentally friendly preparation method. In addition, the addition of nano-silica pore-forming agent increases the interlayer spacing of the molecular structure, and after etching with alkaline solution, a large number of mesoporous structures are formed, which increases the specific surface area of the material and increases the exposure of active sites. In addition, the alkaline solution can selectively dissolve the Al component in the material, only additionally introducing Al vacancy defects without causing other types of defects, thereby forming cation vacancy defects, providing channels for high-speed charge transmission, and improving its electrochemical hydrogen evolution activity.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous nickel-based electrocatalyst containing cation defects, comprising the following steps: S1 raw material mixing: a solution formed by dissolving a certain amount of pore-forming agent in water is mixed with a solution formed by dissolving a certain amount of precursor in a certain amount of deionized water, and the mixture is mixed by ultrasonic and mechanical stirring for 2 hours; the pore-forming agent is monodisperse silica microspheres; the precursor includes soluble nickel salt, soluble aluminum salt, chitosan and accelerator; S2 hydrothermal synthesis: the mixed solution in step 1 is transferred to a polytetrafluoroethylene hydrothermal reactor, and then placed in an oven for constant temperature reaction. After the reaction is completed, the temperature is naturally lowered to ambient temperature, taken out, and centrifuged to obtain a precipitate, which is the reaction product; S3 alkaline solution etching: placing the reaction product of step 2 in alkaline solution and stirring for 12-36 hours for dialysis; S4 washing and drying: washing the sample after etching in step 3 with deionized water and ethanol for several times until the pH of the sample is neutral, and drying the washed sample to obtain a porous nickel-based electrocatalyst (mNiAl-LDH) containing cation defects; S5 electrochemical performance test: 1 mol·L -1 The electrochemical properties of the porous nickel-based electrocatalyst material containing cation defects obtained in step four of the three-electrode test system were tested using KOH as electrolyte, Pt sheet as counter electrode, Hg / HgO as reference electrode, and ITO conductive glass loaded with the sample as working electrode.
2. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: The mixing for 2 hours in step 1 means that after ultrasonication for 30 minutes, magnetic stirring is performed at a speed of 300 rpm for 30 minutes, and the mixture is rotated in sequence and evenly mixed for 2 hours.
3. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: The particle size of the silica microspheres in step 1 is 20-40 nm.
4. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 3, characterized in that: The silica microspheres described in step 1 are dissolved in water to form a silica dispersion with a concentration of 10% w / v.
5. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: In step 1, the soluble nickel salt is one of nickel nitrate, nickel sulfate and nickel chloride, the soluble aluminum salt is one of aluminum nitrate, aluminum sulfate and aluminum chloride, and the promoter is one of urea and hexamethylenetetramine (HMT).
6. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: In step 1, the molar ratio of the promoter / soluble nickel salt is 1:1-5:1, the molar ratio of the soluble nickel salt / soluble aluminum salt is 1:1-5:1, the molar ratio of the pore-forming agent / soluble nickel salt is 5:1-14:1, and the molar ratio of chitosan to the soluble nickel salt is 1:10-1:15; the amount of deionized water used is 65wt% of the total mass of the solution.
7. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: The reaction temperature of step 2 is increased from 30°C at a rate of 1°C / min to 100-140°C, and the reaction is maintained at a constant temperature for 12-48 hours.
8. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: The specific operation of step three is to ultrasonically disperse the reaction product of step two in 50 mL of deionized water again, transfer it to one side of the H-type reactor, add 50 mL of alkali solution on the other side, place an anion exchange membrane in the middle of the channel, stir for 12-36 hours for dialysis, set the temperature to 50-70°C, and the stirring speed to 200 rpm.
9. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 8, characterized in that: The alkali solution in step 3 is one of NaOH and KOH solutions, with a concentration of 6-10 mol·L -1 ; The thickness of the anion exchange membrane is 20-50μm.
10. The method for preparing a porous nickel-based electrocatalyst containing cation defects according to claim 1, characterized in that: The drying step in step 4 is to place the washed sample in an oven at 60°C and dry it for 12 hours.
Citation Information
Patent Citations
CNTs@SiO2@Ni / Al-LDH shell structure three-dimensional nanometer material and preparation method thereof
CN104843805A
Nickel-based electrolysis hydrogen evolution porous cathode material and preparation method thereof
CN109280811A
Preparation method of Co-Ni-P / fs-Si material for hydrogen evolution by electrolyzing water
CN110607532A
Nickel-based electrocatalyst supported by porous nickel, preparation method of nickel-based electrocatalyst and application of nickel-based electrocatalyst in hydrogen production by electrolysis of water
CN116065184A